Leaving no-one behind? Social inequalities and contrasting development impacts in rural Rwanda. (1st January 2018) - Dawson, Neil M.
ABSTRACT: Two polar viewpoints have emerged regarding Rwanda's post-genocide development: (1) that economic development has improved the wellbeing of Rwandans and (2) that repressive policies have negatively impacted many. Assessing the impacts and inclusiveness of policies through trends among different social groups is timely in the context of the Sustainable Development Goals' pledge to 'leave no-one behind'. This study examines rural Rwandans' perspectives on the changes affecting them. A multidimensional wellbeing approach was applied through mixed-method research involving 115 rural households in two locations in western Rwanda, in 2011–12. Findings reveal that the household-level impact was heavily influenced by socio-economic power and socio-ethnic grouping. Negative impacts, including restricted freedom and loss of material and cultural resources are disproportionately felt by the poorest. The indigenous Batwa suffer particularly detrimental impacts. The findings suggest that strategies deemed successful in making progress towards the Millennium Development Goals in Rwanda need, as a minimal measure, to be supported by social protection programs that specifically target the landless, vulnerable and cultural minorities. However, to align Rwanda's development policies with the ambitions of the Sustainable Development Goals (SDGs), a dramatic strategic shift is required to 'leave no-one behind' and avoid the reproduction of poverty and exacerbation of inequality.